Volatile profiling as a potential biochemical marker for validation of gamma irradiation derived putative mutants in polyembryonic genotypes of mango (Mangifera indica L.) - Perveen, Nusrat; Dinesh, M. R.; Sankaran, M.; Shivashankara, K. S.; Ravishankar, K. V.; Venugopal, R.; Mir, Hidayatullah (Frontiers in Plant Science, 2023)
Introduction Putative mutants were generated through gamma irradiation in the polyembryonic mango genotype Nekkare. The putative mutant progenies along with control seedlings and mother plants were evaluated by comparing the compositions and relative proportions of their major volatile compounds. Methods Volatile profiling was done using headspace-solid phase micro-extraction (HS SPME) method coupled with gas chromatography–mass spectrometry (GC-MS MS). Furthermore, characterisation of putative mutants and control seedlings was carried out using simple sequence repeat (SSR) markers to ascertain the genetic diversity present in the samples under study. Results Monoterpenes were the most abundant volatile compound in all the studied samples (ranging from 34.76% to 91.41%) out of which I-Phellandrene and cis-Ocimene formed the major fraction in mother plants (20.45%–21.86% and 16.17%–21.27%, respectively) and control seedlings (23.32%–24.95% and 18.95%–20.81%, respectively), while beta-Phellandrene was dominant in the selected putative mutant samples (2.34%–29.53%). Among sesquiterpenes, trans-Caryophyllene was detected only in the putative mutant samples (0.10%–30.18%). Grouping together of mother plants and control seedlings was seen in the cluster analysis, while the putative mutants grouped apart from them suggesting genetic diversity. Genetic distance between the mother plants and control seedlings ranged from 0.97 to 2.73, while between putative mutants, control seedlings, and mother plants, it ranged from 6.54 to 9.82. SSR-based characterisation of putative mutant seedlings showed that mutation caused variability in the treated population. This was evident from the high allelic richness ranging from 4 to 12 with a mean of 7 and a higher mean Shannon’s Information Index (1.50) of the putative mutant population. Discussion The study demonstrates that volatile profiling and molecular characterisation using SSR markers could be used as a tool to detect variation in a mutated population. In addition, volatile profiling can be used to validate putative mutants in polyembryonic mango genotypes where the seedlings of nucellar origin are similar to mother plants.